Gentrification and UN 2020 – 2030 Agenda - Stefano Aragona (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
But is it right that historic centres, the most prized places in cities, are subject to gentrification? In other words, the expulsion of the original residents and traditional, historical activities, which are the soul of these places: something that is well highlighted in 2000 European Landscape Convention. There are some paradoxes that link the protection policies in place for some years to their results. The pedestrian islands born in Italy nearly 40 years ago with the first pedestrianization of the Colosseum and then the ZTL, initially opposed by the traders, in the medium-long period have meant spread of shops for high incomes and international stores that have supplanted the historic shops. The ecological transformation of a part of the twentieth-century High Line in Manhattan has led to an increase in the real estate values of the area that is growth in sales prices and rents and therefore the replacement of residents and activities. The challenge we face today is how to maintain the identity of places that are transformed or even just recovered, also to make them sustainable as required by the UN. And how to preserve their human component, essential part of this identity, even among the objectives of the Charter 2020-2030.